Foundations of Dominant-Strategy Mechanisms - Chung, Kim-Sau; Ely, J.C. (Review of Economic Studies, 2007)
Robert Wilson criticizes applied game theory's reliance on common-knowledge assumptions. In reaction to Wilson's critique, the recent literature of mechanism design has adopted the goal of finding detail-free mechanisms in order to eliminate this reliance. In practice this has meant restricting attention to simple mechanisms such as dominant-strategy mechanisms. However, there has been little theoretical foundation for this approach. In particular it is not clear the search for an optimal mechanism that does not rely on common-knowledge assumption would lead to simpler mechanisms rather than more complicated ones. This paper tries to fill the void. In the context of an expected revenue maximizing auctioneer, we investigate some foundations for using simple, dominant-strategy auctions.